Synthesis and tissue distribution of fluorine-18-labeled trifluorohexadecanoic acids. Considerations in the development of metabolically blocked myocardial imaging agents - Pochapsky, Susan Sondej; VanBrocklin, Henry F; Welch, Michael J; Katzenellenbogen, John A (Bioconjugate chemistry, 1990)
A versatile method for the synthesis of trifluoro fatty acids, potential metabolically blocked myocardial imaging agents, has been developed. Two trifluorohexadecanoic (palmitic) acids have been prepared [6,6,16-trifluorohexadecanoic acid (I) and 7,7,16-trifluorohexadecanoic acid (II)], each of which bears two of the fluorine atoms as a gem-difluoromethylene unit on the fatty acid chain (at C-6 or C-7) and the third at the omega (C-16) position. The metabolic stability of carbon-fluorine bonds suggests the gem-difluoro group may block the beta-oxidation pathway, while the terminal fluorine could be the site for labeling with fluorine-18. The convergent synthetic approach utilizes a 2-lithio-1,3-dithiane derived from 10-undecenal or 9-decenal, which is alkylated with the OBO (oxabicyclooctyl) ester of 5-bromopentanoic acid or 6-bromohexanoic acid, respectively. Hydroboration-oxidation and alcohol protection are followed by halofluorination to convert the 1,3-dithiane system to a gem-difluoro group. The third fluorine is introduced by fluoride ion displacement of a trifluoromethanesulfonate. This synthesis is adapted to the labeling of these trifluoro fatty acids with the short-lived radionuclide fluorine-18 (t1/2 = 110 min), with the third fluorine introduced as fluoride ion in the penultimate step. The radiochemical syntheses proceed in 3-34% radiochemical yield (decay corrected), with an overall synthesis and purification time of 90 min. Tissue distribution studies in rats were performed with I and II, as well as with 16-[18F]fluoropalmitic acid (III), [11C]palmitic acid, and [11C]octanoic acid. The heart uptake of the fluoropalmitic acids decreases with substitution, the 2-min activity level for 16-fluoropalmitic acid being 65% and that for both 6,6,16- and 7,7,17-trifluoropalmitic acids being 30% that of palmitic acid. Fluorine substitution results in some alteration in the retention of activity by the heart: 16-fluoropalmitate actually clears more rapidly than palmitate, but the two trifluoropalmitates (particularly 6,6,16-trifluoropalmitate, I) show somewhat slower clearance of activity, although the improvement of I over palmitate is only modest. There is considerable accumulation of activity in the bone after administration of the fluorine-18 labeled fatty acids, suggestive of metabolic defluorination. These results indicate that fluorine substitution alters the physicochemical properties of the fatty acid so that uptake by the myocardium is diminished. Furthermore, while the gem-difluoro substituents at C-6 and C-7 may block beta-oxidation, the chain-terminal radiofluorine substituent is subject to omega-oxidation that releases it as fluoride ion.